Analisis Kejadian Banjir ROB di Provinsi Bengkulu Periode 2022-2024 - Agustina, Lisa Asyifa; Lubis, Ashar Muda; Pranowo, Widodo Setiyo (Universitas Diponegoro, 2025)
Bengkulu Province is one of the coastal areas prone to tidal flooding due to a combination of various oceanographic and meteorological factors such as tides, wind speed, rainfall, and sea wave height. This study aims to analyze the dominant factors causing tidal floods in Bengkulu Province during the period 2022-2024. Data on tidal flood events were obtained from BPBD and BPS reports of Bengkulu Province, as well as mass media sources. The analysis was conducted using wind data from the European Center for Medium Weather Forecast (ECMWF), rainfall data from the Meteorology, Climatology and Geophysics Agency (BMKG), and tidal prediction data from the Geospatial Information Agency (BIG). The results show that during the west season, tidal floods are triggered by strong westerly winds due to the West Monsoon, full tides, and moderate to high rainfall, as in the events of February 4-6, 2022 and January 26-27, 2023. During the east monsoon, tidal floods are caused by steady southeast winds and high tides due to the East Monsoon, despite low rainfall, as in the events of July 30, 2023 and August 3-5, 2023. In the transitional season, tidal floods tend to be influenced by a combination of full tides, moderate winds and light to moderate rainfall, such as on May 14-15, 2022 and October 16-17, 2024. Factors such as tropical cyclone activity and the Indian Ocean Dipole (IOD) also contribute significantly to the increased risk of tidal flooding, particularly strengthening winds and increasing rainfall in certain seasons. Provinsi Bengkulu merupakan salah satu wilayah pesisir yang rawan terkena banjir rob akibat kombinasi berbagai faktor oseanografis dan meteorologis seperti pasang surut, kecepatan angin, curah hujan, dan tinggi gelombang laut. Penelitian ini bertujuan untuk menganalisis faktor dominan penyebab banjir rob di Provinsi Bengkulu selama periode 2022–2024. Data kejadian banjir rob diperoleh dari laporan BPBD dan BPS Provinsi Bengkulu, serta sumber media massa. Analisis dilakukan dengan menggunakan data angin dari European Center for Medium Weather Forecast (ECMWF), data curah hujan dari Badan Meteorologi, Klimatologi, dan Geofisika (BMKG), serta data prediksi pasang surut dari Badan Informasi Geospasial (BIG). Hasil penelitian menunjukkan bahwa pada musim barat, banjir rob dipicu oleh angin barat yang kuat akibat Monsun Barat, pasang purnama, dan curah hujan sedang hingga tinggi, seperti pada kejadian 4–6 Februari 2022 dan 26–27 Januari 2023. Selama musim timur, banjir rob disebabkan oleh angin tenggara yang stabil dan gelombang tinggi akibat Monsun Timur, meskipun curah hujan rendah, seperti pada kejadian 30 Juli 2023 dan 3–5 Agustus 2023. Pada musim peralihan, banjir rob cenderung dipengaruhi oleh kombinasi pasang purnama, angin sedang, dan curah hujan ringan hingga sedang, seperti pada 14–15 Mei 2022 dan 16–17 Oktober 2024. Faktor-faktor seperti aktivitas tropikal siklon dan Indian Ocean Dipole (IOD) juga memberikan kontribusi signifikan terhadap peningkatan risiko banjir rob, terutama memperkuat angin dan meningkatkan curah hujan pada musim tertentu.